Lipoprotein-Associated Phospholipase A2: A Novel Contributor in Sjögren’s Syndrome-Related Lymphoma? - Nezos, Adrianos; Skarlis, Charalampos; Psarrou, Anna; Markakis, Konstantinos; Garantziotis, Panagiotis; Papanikolaou, Asimina; Gravani, Fotini; Voulgarelis, Michael; Tzioufas, Athanasios G.; Koutsilieris, Michael; Moutsopoulos, Haralampos M.; Kotsifaki, Eleni; et al. (Frontiers in Immunology, 2021)
Background: B-cell non-Hodgkin's lymphoma (B-NHL) is one of the major complications of primary Sjögren’s syndrome (SS). Chronic inflammation and macrophages in SS minor salivary glands have been previously suggested as significant predictors for lymphoma development among SS patients. Lipoprotein-associated phospholipase A2 (Lp-PLA2) -a product mainly of tissue macrophages- is found in the circulation associated with lipoproteins and has been previously involved in cardiovascular, autoimmune and malignant diseases. Objective: The purpose of the current study was to investigate the contributory role of Lp-PLA2 in B-NHL development in the setting of primary SS. Methods: Lp-PLA2 activity in serum samples collected from 50 primary SS patients with no lymphoma (SS-nL), 9 primary SS patients with lymphoma (SS-L) and 42 healthy controls (HC) was determined by detection of [3H]PAF degradation products by liquid scintillation counter. Moreover, additional sera from 50 SS-nL, 28 SS-L and 32 HC were tested for Lp-PLA2 activity using a commercially available ELISA kit. Lp-PLA2 mRNA and protein expression in minor salivary gland (MSG) tissue samples derived from SS-nL, SS-L patients and sicca controls (SC) were analyzed by real-Time PCR, western blot and immunohistochemistry. Results: Serum Lp-PLA2 activity was significantly increased in SS-L compared to both SS-nL and HC by two independent methods implemented [mean±SD (nmol/min/ml): 62.0±13.4 vs 47.6±14.4 vs 50.7±16.6, p-values: 0.003 and 0.04, respectively and 19.4±4.5 vs 15.2±3.3 vs 14.5±3.0, p-values: <0.0001, in both comparisons]. Lp-PLA2 expression in MSG tissues was also increased in SS-L compared to SS-nL and SC at both mRNA and protein level. ROC analysis revealed serum Lp-PLA2 activity measured either by radioimmunoassay or ELISA, as well as MSG mRNA and protein Lp-PLA2 have the potential to distinguish between SS-nL and SS-L patients [area under the curve (AUC): 0.8022, p-value: 0.004 for radioimmunoassay; 0.7696, p-value: <0.0001 for ELISA; 0.8490, p-value: 0.0019 for MSG mRNA expression and 0.9444, p-value: 0.0389 for MSG protein expression]. No significant difference in either serum Lp-PLA2 activity or MSG tissue expression was observed between SS-nL and HC. Conclusions: Lp-PLA2 serum activity and MSG tissue mRNA/protein expression could potentially serve as a novel biomarker and therapeutic target for SS related B-cell lymphoproliferation.